An amphipathic cell penetrating peptide aids cell penetration of cyclosporin A and increases its therapeutic effect in an in vivo mouse model for dry eye disease. Issue 91 (9th October 2019) - Hyun, Soonsil; Li, Lan; Yoon, Kyung Chul; Yu, Jaehoon
Abstract : The use of CPP, LK-3, increases the cell penetration of cyclosporine A (CsA) at nanomolar concentrations and therapeutic efficacy. Abstract : Cell penetrating peptide (CPP), LK-3, causes a ca. 10-fold increase in the cell penetration of cyclosporin A (CsA) at nanomolar concentrations. The results of an in vivo dry eye mouse model demonstrated that a 100-fold lower dose of the CsA/LK-3 complex than that of Restasis® is sufficient to cause the same therapeutic effect.